MEDIA USED FEMALE SEX WORKER IN SEXUAL HEALTH MANAGEMENT (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Localization and female sex workers are a complex social problem. Social and health problems are a form of complexity. Solutions to problems are interrelated and simultaneous because the characteristics and patterns of communication in localization, especially those which is done by female sex workers have their own characteristics. Negative labeling given by the community to this group become the identifier or differentiator in their patterns and characteristics in communicating within the group. The focus of his research was the use of health communication media for female sex workers in health management to overcome Sexually Transmitted Infections (IMS) and their group interactions through qualitative descriptive research with case studies. The informants involved were the main and key informants where the main informants took the peer educator for female sex workers and representatives of female sex workers who did not include peers. While key informants are involving parking men and pimps. The result of this study is that the use of health media by female sex workers has a typology that depends on the characteristics of the group. Likewise, the success of health management depends on massive and appropriate media use. The effectiveness of media can be obtained from group communication whose communication approach cannot be equated.